2020
DOI: 10.1097/mcg.0000000000001444
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Serum Pepsinogen Level With the Risk of Gastric Precancerous Conditions

Abstract: Background and Aim: Gastric precancerous conditions are generally considered to play an essential role in the gastric carcinogenesis cascade. This study identified risk factors of gastric precancerous conditions in a nationwide multicenter cross-sectional study.Methods: Individuals who made their visit to 115 hospitals in China for gastric cancer screening were recruited. Lifestyle habits and personal information were collected through a series of questionnaires. Serum biomarker test (pepsinogen I, pepsinogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The results of the ROC curve analysis showed that G-17 had high sensitivity for the diagnosis of early gastric cancer, but the specificity was not high. Combined with previously reported analyses, the level of G-17 may be affected by many factors, such as eating habit, gastric lesion location, drugs, and G-cell number, so in clinical practice, it is not effective to use G-17 alone as a diagnostic reference indicator (13).…”
Section: Discussionmentioning
confidence: 91%
“…The results of the ROC curve analysis showed that G-17 had high sensitivity for the diagnosis of early gastric cancer, but the specificity was not high. Combined with previously reported analyses, the level of G-17 may be affected by many factors, such as eating habit, gastric lesion location, drugs, and G-cell number, so in clinical practice, it is not effective to use G-17 alone as a diagnostic reference indicator (13).…”
Section: Discussionmentioning
confidence: 91%
“…The logistic regression analysis in Table 4 of this study further confirms the correlation between these factors and Hp infection. [ 18 ] Intestinal metaplasia refers to the phenomenon where the gastric mucosal epithelial cells transform into a structure resembling intestinal epithelium. This may lead to a decrease in gastric mucosal acidity.…”
Section: Discussionmentioning
confidence: 99%
“…Other significant risk factors were H. pylori infection and pepsinogen I level (odds ratios of 1.377 and 1.536, respectively). Diet consisted of high fat had protective effect with odds ratio of 0.731 ( 17 ). Ajdarkosh et al supported the previous results.…”
Section: Discussionmentioning
confidence: 99%